China's Expressways : Connecting People and Markets for Equitable Development - World Bank (Washington, DC, 2012)
This paper, prepared in response to the Chinese government's request, examines the institutional and financial arrangements under which the expansion of the Chinese expressway network has taken place. China's outstanding achievements in economic growth and poverty reduction over the last fifteen years have been well documented. The major emphasis has been on the development of its infrastructure, particularly transport. All modes of transport have seen their networks expanded, to provide the infrastructure needed to support the broader development goals. Road transport is vitally important and, among the surface modes, has seen its share grow over the last ten years from 45 percent to 60 percent in terms of passenger-km and from 24 percent to 30 percent in terms of freight ton-km. The road transport system has contributed greatly to china's continuing economic and social development. The expansion of the road network during the last 20 years was made possible by rapid increases in public funding. Since 1990, the overall average growth in the Chinese road assets has exceeded the overall growth in its Gross Domestic Product (GDP) and has helped to close the 'infrastructure gap' that existed at the beginning of the period.